Effect of a Dietary Supplement Combination on Weight Management, Adipose Tissue, Cholesterol and Triglycerides in Obese Children - González, Michael J.; Miranda-Massari, Jorge R.; Ricart, Carlos M.; Guzmán, Angélica M. (Puerto Rico Health Sciences Journal, 2005)
A dietary supplement combination consisting of vitamins, minerals and fibers was studied to determine its safety and efficacy on weight/fat loss, cholesterol and triglycerides in children between ages 7-13. This open label trial measured total body weight, body fat percentage, waist circumference, total cholesterol, triglycerides before and after 6 weeks of treatment. The study population consisted of 25 mildly to moderate obese, otherwise healthy children of both sexes. After 6 weeks of treatment, the combination supplement had a statistically significant (p < 0.05) weight reducing effect. This weight reduction was associated with a corresponding statistically significant (p < 0.0001) decrease in body fat percentage. In addition, significant decreases in total cholesterol (p < 0.0001) and triglycerides (p < 0.0001) were obtained, plus reductions in waist measurements. We conclude that the combination supplement studied herein is a safe and effective way to assist children in weight, fat percentage, cholesterol and triglyceride reduction.